Glucose biosensing at carbon paste electrodes containing iron nanoparticles - Comba, Fausto Nahuel (2010)
This work reports the advantages of incorporating a metal as common as iron in a carbon paste electrode containing glucose oxidase to develop highly selective, stable and sensitive amperometric glucose biosensors. The excellent catalytic activity of iron nanoparticles towards the reduction of hydrogen peroxide has made possible the quantification of glucose at very low potentials (-0.100 V) avoiding, in this way, the interference of easily oxidizable compounds like ascorbic acid and uric acid without needing of redox mediators or permselective membranes. Linear relationship between current and glucose concentration was obtained up to 0.020 M (3.6 g/L), with a detection limit of 0.2 mM, no interference of AA and UA, and very good correlation with the spectrophotometric methods when determining glucose in human blood serum. © 2010 Elsevier B.V. All rights reserved.